Illicit Economies Through the Lens of Urban Peace: Towards a New Policy Agenda - Achim Wennmann (Journal of Illicit Economies and Development, 2021)
This article draws together and discusses the key practical lessons of this Special Issue as a means to revisit ‘urban peace’ as a policy framework. It positions responses to illicit economies within a broader socio-economic agenda for which the notion of ‘urban peace’ acts as an umbrella for expanding the toolbox for dealing with illicit economies and as a signpost for the direction of policies to achieve greater levels of negative and positive peace. The agenda prioritizes the expansion of economic opportunities in informal economies as a critical strategic objective to manage the pressures within rapidly growing cities and to ensure peaceful urban politics in turbulent times. The article starts by charting the current mainstream responses to illicit economies before discussing the lessons of alternatives to law and order approaches of different case studies. It highlights multidimensional approaches and strong coordination mechanisms, as well as the potential of platform models as governance mechanisms for programmes to transform illicit economies. The article also underlines how illicit economies create their own non-state forms of order in which violence has a functional purpose. Building on a political economy perspective, the article proposes pragmatic peacebuilding and urban political settlements as a means to regulate and transform illicit economies. In the face of major systemic shifts happening over the next decade, the article underlines the need for a more fundamental rethink about how cities should address the multitude of challenges they are facing.